Natural Language Processing (NLP) - G, Dr. Chandrika (International journal for research in applied science and engineering technology, 2024)
Machines utilize Natural Language Processing (NLP), a subfield of Artificial Intelligence (AI), to comprehend, evaluate, and translate human languages. Due to advancements in information and communication technology over the last ten years, NLP has gained increased awareness and has been the subject of several studies. Understanding the steps required to advance literary understanding is so crucial. The study's objective is to provide an organized review of the literature in NLP research using bibliometric analysis. In the discipline of NLP, the study highlights important research fields, research clusters, cited publications, significant authors, institutions, nations, and publishing patterns. From the Web of Science (WoS) database, 12541 NLP papers were taken out and subjected to further bibliometric analysis The outcome showed that the largest number of NLP publications occurred in 2021, with the first publication being in 1989. The leading journal with the most publications was IEEE Access, and NLP papers have earned the most citations—3174—than any other journal. Liu HF is the most productive author in the field of NLP, and Harward University is the most significant organization. When it comes to the overall amount of publications, the US is the top nation. Researchers looked at the applied sciences in great detail.